2011
DOI: 10.1002/eji.201141825
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in human colorectal cancer are pro‐inflammatory and prime T cells towards an anti‐tumour type‐1 inflammatory response

Abstract: High macrophage infiltration into tumours often correlates with poor prognoses; in colorectal, stomach and skin cancers, however, the opposite is observed but the mechanisms behind this phenomenon remain unclear. Here, we sought to understand how tumour-associated macrophages (TAMs) in colorectal cancer execute tumoursuppressive roles. We found that TAMs in a colorectal cancer model were pro-inflammatory and inhibited the proliferation of tumour cells. TAMs also produced chemokines that attract T cells, stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 35 publications
3
100
0
2
Order By: Relevance
“…The ability of cytokine-producing T cells to skew myeloid subsets is emphasized by the observation that the absence of CD8 T cells in skin wounds also decreases macrophage infiltration (38). At the same time, modified macrophages within the tumor might boost an antitumor type I inflammatory response (39) and previous studies showed that CSF-1R-triggering enhanced the tumoricidal capacity of macrophages (40). Importantly, these studies together reveal the large plasticity of the intratumoral myeloid population and indicate that conventional and immune-based treatments can polarize the tumor-promoting function of macrophages into tumor-rejection responses.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cytokine-producing T cells to skew myeloid subsets is emphasized by the observation that the absence of CD8 T cells in skin wounds also decreases macrophage infiltration (38). At the same time, modified macrophages within the tumor might boost an antitumor type I inflammatory response (39) and previous studies showed that CSF-1R-triggering enhanced the tumoricidal capacity of macrophages (40). Importantly, these studies together reveal the large plasticity of the intratumoral myeloid population and indicate that conventional and immune-based treatments can polarize the tumor-promoting function of macrophages into tumor-rejection responses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies find that, TAMs mainly exhibit anti-tumor effects in colorectal cancer. Ong et al (2012) have investigated the colorectal cancer models and find that, TAMs can secrete chemokines and promote T cell proliferation, thus activate type 1 T cell responses and exert anti-tumor effects. Kinouchi et al (2011) have studied 52 colorectal cancer specimens and found that, CD14 + macrophages are mainly distributed in tumor invasive front, and the 5-year survival rate of patients with large number of CD14 + macrophages is higher than patients with small number of CD14 + macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Pander et al (72) reported that the M2 phenotype predominated in the tumors of 10 patients with untreated stage III CRC, as determined by immunohistochemical staining for CD163. Ong et al (71) found that the percentage of proinflammatory macrophages (M1), measured by double immunofluorescence for CD68 and IFN-␥, in tumors from five patients with CRC were 6.6, 8.3, 16, 31, and 50% (71). The most extensive study was recently performed by Edin et al (20), where colorectal tumors from 485 patients were evaluated for the presence of iNOS, an M1 marker, and CD163, an M2 marker.…”
Section: Macrophage Phenotype In Crcmentioning
confidence: 99%